Contextualising sex and gender research to improve women's health: An early- and mid-career researcher perspective - Hallam, Laura; McKenzie, Briar L.; Gong, Jessica; Carcel, Cheryl; Hockham, Carinna (Frontiers in Global Women's Health, 2022)
The field of sex and gender research in health and medicine is growing, and many early and mid-career researchers (EMCRs) are developing skills in this area. As EMCRs specialising in sex and gender research, we aim to better understand sex- and gender-based determinants of human health, challenge long-standing and pervasive gender biases, and contribute to improving the evidence base upon which clinical guidelines and policy interventions are developed. To effectively achieve these goals, we believe that EMCRs would benefit from understanding the challenges working in this space and participate in driving change in three key areas. First, in creating greater links between the goals of sex and gender research and addressing systemic bias against women and gender minorities, to effectively translate knowledge about sex and gender differences into improved health outcomes. Second, in expanding the reach of sex and gender research to address women’s health in an intersectional way and ensure that it also benefits the health of men, transgender and gender-diverse people and those who are intersex. Third, in working with others in the scientific community to improve methods for sex and gender research, including updating data collection practices, ensuring appropriate statistical analyses and shifting scientific culture to recognise the importance of null findings. By improving focus on these three areas, we see greater potential to translate this research to improve women’s health and reduce health inequities for all.